Video Recording of the On-site Investigation - Constantin RUSNAC; Nicolai LEVANDOVSKI (ACROSS)
Currently, the increasing effectiveness of criminal procedural investigations is determined by the level of implementation in the practical activity of methods and technical-scientific means intended for discovery, fixation, collection, and examination through which the missing data omitted by the person in the process of perception, memorization, saving, reproduction, systematization, and transmission of information are compensated.